Minority report [videorecording (DVD)] - Spielberg, Steven, 1946-; Cruise, Tom, 1962-; Farrell, Colin, 1976-; Morton, Samantha; Sydow, Max von, 1929-2020; Smith, Lois, 1930-; Stormare, Peter; Nelson, Tim Blake; Harris, Steve, 1965-; Morris, Kathryn; Binder, Mike, 1958-; London, Daniel, 1973-; et al. (DreamWorks Home Entertainment : Distributed by Twentieth Century Fox Film Corp., 2003)
Washington, D.C. has been murder-free thanks to astounding technology which identifies killers before they commit their crimes. But when the chief of the pre-crime unit is himself accused of a future murder, he has just 36 hours to discover who set him up.